HIV Incidence in Botswana Rural Communities With High Antiretroviral Treatment Coverage: Results From the Botswana Combination Prevention Project, 2013–2017. (1st September 2022) - Ussery, Faith; Bachanas, Pamela; Alwano, Mary Grace; Lebelonyane, Refeletswe; Block, Lisa; Wirth, Kathleen; Ussery, Gene; Sento, Baraedi; Gaolathe, Tendani; Kadima, Etienne; Abrams, William; Segolodi, Tebogo; et al.
Abstract : Background and Setting: The Botswana Combination Prevention Project demonstrated a 30% reduction in community HIV incidence through expanded HIV testing, enhanced linkage to care, and universal antiretroviral treatment and exceeded the Joint United Nations Programme on HIV/AIDS 90–90–90 targets. We report rates and characteristics of incident HIV infections. Methods: The Botswana Combination Prevention Project was a community-randomized controlled trial conducted in 30 rural/periurban Botswana communities from 2013 to 2017. Home-based and mobile HIV-testing campaigns were conducted in 15 intervention communities, with 39% of participants testing at least twice. We assessed the HIV incidence rate [IR; number of new HIV infections per 100 person-years (py) at risk] among repeat testers and risk factors with a Cox proportional hazards regression model. Results: During 27, 517 py, 195 (women: 79%) of 18, 597 became HIV-infected (0.71/100 py). Women had a higher IR (1.01/100 py; 95% confidence interval: 0.99 to 1.02) than men (0.34/100 py; 95% confidence interval: 0.33 to 0.35). The highest IRs were among women aged 16–24 years (1.87/100 py) and men aged 25–34 years (0.56/100 py). The lowest IRs were among those aged 35–64 years (women: 0.41/100 py; men: 0.20/100 py). The hazard of incident infection was the highest among women aged 16–24 years (hazard ratio = 7.05). Sex and age were significantly associated with incidence (both P < 0.0001). CONCLUSIONS: Despite an overall reduction in HIV incidence and approaching the United Nations Programme on HIV/AIDS 95–95–95 targets, high HIV incidence was observed in adolescent girls and young women. These findings highlight the need for additional prevention services (pre-exposure prophylaxis and DREAMS) to achieve epidemic control in this subpopulation and increased efforts with men with undiagnosed HIV.